Information in the public health sector from an anthropological perspective: a study carried out in Minas Gerais, Brazil - DOI: 10.3395/reciis.v3i3.287en - José Wanderlei Novato Silva (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
This study examines the relationship between the organizational culture of municipal health secretariats of the State of Minas Gerais, Brazil - from the perspective of managers and employees - and how these players deal with information in the health sector. Organizational culture was een as a shared means of work that established forms of "informational behavior", and values and principles that comprise an "informational culture". This culture was analyzed by taking into consideration, among its external constraints, the local, regional, national and global culture levels. The methodology comprised a qualitative analysis of the health ecretariats of three municipalities deliberately selected. Results showed several different aspects concerning how departments deal with health-related information - in line with aspects of state and national cultures, which oscillate between modernity and backwardness. The study was considered "anthropological" because the author based his analysis on concepts originating from this field of knowledge. The perception of the transdisciplinarity of information in the health sector - political, technical, social, cultural, economic and administrative - intended to understand how the practices and concepts of the public health sector are the bearers of multiple socially conditioned meanings, aiming at broadening the concept of "anthropology of information".